The Influence of Interest and Creativity on Learning Achievement Students of SMKN 1 Tongkuno - Usman, Usman; Badiun, Badiun; Sangi, Nontje (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2022)
This study aims to: 1 determine the effect of interest in learning on student achievement in the electrical installation engineering expertise program 11th class SMK Negeri 1 Tongkuno and 2 To determine the effect of learning creativity on student achievement in the electrical installation engineering skill program 11th class SMK Negeri 1 Tongkuno 3 To determine the effect of interest and creativity on student achievement in the electrical installation engineering expertise program 11th class SMK Negeri 1 Tongkuno The population in this study was all students of class XI a 28 students and students of class XI b 25 students at SMK Negeri 1 Tongkuno with 53 students so this research is a population study Questionnaires and documentation do data collection Questionnaire to collect data on interest and creativity in learning while documentation to collect data on learning achievement This instrument trial was conducted on 35 students of 11th class TITL SMK Negeri 1 Tongkuno; the multiple regression analysis techniques were used in the data analysis The analysis requirements test was conducted before data analysis including normality multicollinearity autocorrelation and heteroscedasticity The result of this study is that 1 learning interest X1 has a significant effect on learning achievement Y which is indicated by a significance value of 000 lt; 023 so that the first hypothesis proposed can be accepted Learning creativity X2 has a significant effect on student achievement Y ; this is indicated by a significance value of 004 lt; 05 so the second hypothesis formulated in this study can be accepted Based on the result of hypothesis testing it claims that student progress in the electrical installation engineering competence program 11th class SMK Negeri 1 Tongkuno is significantly influenced by enthusiasm and creativity it can be proven by the significance value of F F sig of = 000 which means it is smaller than = 05 F sig 000 lt; 05 < strong>< p>